Due to Legal Decisions of the Industrial Relations Court that Exceed the Time Limitation of 50 Working Days Since the First Session - I Made Adiwidya Yowana (UIN Sunan Gunung Djati, 2022)
This study examines the legal consequences of industrial relations court decisions that exceed the time limit of 50 working days from the first trial. This research is normative legal research, which is conducting research by examining various laws and regulations and legal principles related to the settlement of industrial relations disputes. The study results indicate that the industrial relations court's decision is still legally valid even though the decision has passed the time limit of 50 working days from the first trial as regulated in Article 103 of the PPHI Law. This is because the procedural law adheres to lex stricta, which must be interpreted strictly, including the prohibition on the interpretation of analogies. Apart from the principle of lex stricta, the principle of res judicata pro veritate habetur, and the null and void nature of the law, it also confirms that the IRC's decision remains valid even though it violates the provisions of Article 103 of the PPHI Law. Based on the research results, it can be suggested that the Supreme Court immediately issued a Supreme Court Regulation (PERMA) regarding the imposition of administrative sanctions on the industrial relations court judges who violate the provisions of Article 103 of the PPHI Law.